PENINGKATAN KESADARAN PEREMPUAN TERHADAP PENGELOLAAN LINGKUNGAN WILAYAH PESISIR DI KELURAHAN BUMI WARAS BANDAR LAMPUNG - Darmastuti, Ari; Budiono, Pitojo; Maryanah, Tabah; Handayani, Dwi Wahyu (Prosiding Pengabdian FISIP Unila, 2012)
Can be formulated conditions of coastal communities Bandar Lampung, especially in the Village Earth Sane, as follows: (1). Women and children are the most vulnerable due to unhealthy environmental conditions, (2). Knowledge and awareness of the community, especially women in the surrounding environment management is still low, (3). Women and children are the most vulnerable due to weak family economy, so the sustainability of low education and women easily become victims of domestic violence. The method used in this activity is a seminar / lecture on organizational functions, strengthening organizations, gender and the environment, human rights and the environment, and the law on the environment. This activity is also using simulation methods on how to build a strategy of analysis of the problem and its potential, as well as simulations of effective environmental management measures. The results of the activities, participants gain understanding about the organization / institution, gender and the environment, human rights and the environment and socialization of Environmental Law. Keywords: Awareness of Women, Environmental Management, Gender